Saluran Pemasaran Ternak Ayam Broiler di Kelurahan Tiakur Kecamatan Moa Kabupaten Maluku Barat Daya - Yermias, Atalia; Jesajas, Heryanus; Alam, Asmirani (Kalwedo Sains (KASA), 2024)
This study aims to find out the form of the Broiler Chicken Marketing Channel in Tiakur Village, Moa District, Southwest Maluku Regency. This research was carried out in June-August 2024 in Tikur Village. This research was conducted on broiler chicken farmers, collectors and retailers who were traced using the snowball sampling method. This study uses 6 broiler chicken farming businesses in Tiakur Village as respondents and the design used is a descriptive design. The results of the study show that most businesses from broiler chicken farms use short marketing channels compared to long marketing channels. In addition, based on the results of the study, it also shows that the broiler chicken marketing channel in Tiakur Village, Moa District, Southwest Maluku Regency has various problems, including limited market access, high transportation costs, demand, competition with other products, lack of knowledge about marketing strategies, product quality problems and too many intermediaries.